Development of an RT-qPCR assay for the specific detection of a distinct genetic lineage of the infectious bursal disease virus. Issue 2 (4th March 2017) - Tomás, Gonzalo; Hernández, Martín; Marandino, Ana; Techera, Claudia; Grecco, Sofia; Hernández, Diego; Banda, Alejandro; Panzera, Yanina; Pérez, Ruben
ABSTRACT: The infectious bursal disease virus (IBDV) is a major health threat to the world's poultry industry despite intensive controls including proper biosafety practices and vaccination. IBDV ( Avibirnavirus, Birnaviridae ) is a non-enveloped virus with a bisegmented double-stranded RNA genome. The virus is traditionally classified into classic, variant and very virulent strains, each with different epidemiological relevance and clinical implications. Recently, a novel worldwide spread genetic lineage was described and denoted as distinct (d) IBDV. Here, we report the development and validation of a reverse transcription-quantitative polymerase chain reaction (RT-qPCR) assay for the specific detection of dIBDVs in the global poultry industry. The assay employs a TaqMan-MGB probe that hybridizes with a unique molecular signature of dIBDV. The assay successfully detected all the assessed strains belonging to the dIBDV genetic lineage, showing high specificity and absence of cross-reactivity with non-dIBDVs, IBDV-negative samples and other common avian viruses. Using serial dilutions of in vitro -transcribed RNA we obtained acceptable PCR efficiencies and determination coefficients, and relatively small intra- and inter-assay variability. The assay demonstrated a wide dynamic range between 10 3 and 10 8 RNA copies/reaction. This rapid, specific and quantitative assay is expected to improve IBDV surveillance and control worldwide and to increase our understanding of the molecular epidemiology of this economically detrimental poultry pathogen.